Redescription of the Ant Leptothorax (S. STR.) Scamni Ruzsky, 1905 - J. Heinze; A. Schulz; A. G. Radchenko (Psyche: A Journal of Entomology)
Worker and queen caste of the ant Leptothorax (sensu stricto) scamni Ruzsky, 1905 are formally described and a neotype is designated. The species is distinguished from other Leptothorax (s. str.) by extraordinarily long, finger-shaped propodeal spines. L. scamni appears to be a rather rare, patchily distributed ant in alpine coniferous forests in the Caucasus (Russia and Armenia) and northern Turkey.